Huculszczyzna w II Rzeczpospolitej Polskiej. Romantyczny mit „Nowej Arkadii” w racjonalnym społeczeństwie/ Hutsul Region in the Second Republic of Poland. The Romantic Myth of the "New Arcadia" in Rational Society - Włodzimierz Osadczy (Language, Culture, Politics)
In the Second Republic of Poland, the Hutsul region was shown as a semi-wild, picturesque land, shrouded in folk mythology and magic. It was perceived as a center of life unspoiled by civilization, possessing great energy and spontaneity. A specific stereotype of the Hutsul region as an idealized land has developed, where the best qualities that characterize the area, people, and tradition have merged into a very attractive model of social life. The values of the Hutsul region were revealed to Poles in various areas of social interest such as tourism, art or travel